Mediating roles of college teaching self-efficacy in job stress and job satisfaction among Chinese university teachers - Liu, Yanling; Yi, Soohyun; Siwatu, Kamau O. (Frontiers in Education, 2023)
The present study aimed to extend understanding of a mediating effect of college teaching self-efficacy (CTSE) on the relationship between faculty job stress and job satisfaction. Data collected from 455 Chinese university teachers were analyzed using structural equation moderated mediation models. CTSE was an effective mediator in alleviating the negative relationship between job stress and job satisfaction. Our finding from a moderated mediation model suggests that the mediation effect of CTSE did not differ by teaching experience, ranks, gender, and workload. However, the significant covariate effect of teaching experience incorporated in the mediation effect implies that teachers with more teaching experiences may have greater teaching self-efficacy, which may positively change the perceptions of job stress and job satisfaction. Some impractical implications are further discussed.